2020
DOI: 10.1111/cyt.12901
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer diagnosed on cervical cytology

Abstract: An unusual case is described of a 64‐year‐old woman with a remote history of breast cancer whose first non‐nodal metastasis was discovered on a routine Pap test. The Pap test was supported by the results of cervical and endometrial biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Examples of HPV-independent malignant lesions that may escape detection by routine screening include metastatic carcinomas, carcinoma cells shed from the urinary bladder and upper female genital tract, and local spread from pelvic (mostly colorectal and genitourinary) carcinomas. [5][6][7] These lesions can develop rapidly within screening intervals, and similar to our case, show no HPV-related effects or lesions in the background. Furthermore, primary HPVindependent malignancies, such as melanomas and lymphomas, 4,9 can be locally limited and clinically unnoticed, inappropriately implying an even lower index of suspicion for malignancy.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Examples of HPV-independent malignant lesions that may escape detection by routine screening include metastatic carcinomas, carcinoma cells shed from the urinary bladder and upper female genital tract, and local spread from pelvic (mostly colorectal and genitourinary) carcinomas. [5][6][7] These lesions can develop rapidly within screening intervals, and similar to our case, show no HPV-related effects or lesions in the background. Furthermore, primary HPVindependent malignancies, such as melanomas and lymphomas, 4,9 can be locally limited and clinically unnoticed, inappropriately implying an even lower index of suspicion for malignancy.…”
Section: Discussionsupporting
confidence: 80%
“…Examples of HPV‐independent malignant lesions that may escape detection by routine screening include metastatic carcinomas, carcinoma cells shed from the urinary bladder and upper female genital tract, and local spread from pelvic (mostly colorectal and genitourinary) carcinomas 5‐7 . These lesions can develop rapidly within screening intervals, and similar to our case, show no HPV‐related effects or lesions in the background.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A concise literature review of reported cases of breast cancer metastases to the cervix, adapted from Horikawa et al and Proença et al, revealed a total of 19 cases [17,18]. In this literature review (Table 1), of the 19 patients -including our case -there was an almost equal distribution of invasive lobular carcinoma and invasive ductal carcinoma, 11 and 8 cases, respectively [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. This review demonstrated that presenting symptom leading to the discovery of metastasis to the cervix was abnormal vaginal bleeding in 12 out of 19 patients.…”
Section: Discussionmentioning
confidence: 86%
“…A concise literature review of reported cases of breast cancer metastases to the cervix, adapted from Horikawa et al and Proença et al, revealed a total of 19 cases [ 17 , 18 ]. In this literature review (Table 1 ), of the 19 patients - including our case - there was an almost equal distribution of invasive lobular carcinoma and invasive ductal carcinoma, 11 and 8 cases, respectively [ 17 - 32 ].…”
Section: Discussionmentioning
confidence: 97%